1972
DOI: 10.1029/ja077i016p02851
|View full text |Cite
|
Sign up to set email alerts
|

Some implications of satellite spin effects in cylindrical probe measurements

Abstract: In situ measurements of ambient electron densities with satellite‐borne cylindrical probes exhibit periodic variations synchronous with the satellite spin cycle. Representing these fluctuations as a superposition of effects attributable to both the presence of the satellite wake and the geomagnetic field leads to a model of the modulations of accelerated electron current to cylindrical probes in which one modulation component displays current variations dependent on the probe velocity angle (ψ), and the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Experiments on board an elliptical-orbit satellite 16 and a rocket, 17 covering a broad range of altitudes, did show a current dependent on the angle between B and a cylindrical probe ͑B-effects͒ when N ϱ dropped low enough, at very low and high altitudes. In all such experiments, probe bias was only moderately high, however.…”
Section: Equation ͑32͒mentioning
confidence: 99%
“…Experiments on board an elliptical-orbit satellite 16 and a rocket, 17 covering a broad range of altitudes, did show a current dependent on the angle between B and a cylindrical probe ͑B-effects͒ when N ϱ dropped low enough, at very low and high altitudes. In all such experiments, probe bias was only moderately high, however.…”
Section: Equation ͑32͒mentioning
confidence: 99%
“…Another perturbation comes from the magnetic field effect on the trajectories of the particles. This has been experimentally detected [Miller, 1972] and theoretically analyzed in some particular cases [Whipple, 1965;Lafon, 1973].…”
Section: Introductionmentioning
confidence: 99%
“…They found that magnetic effects are important, even when the wire radius is small compared to the electron gyroradius, if the latter is less than the thickness of the plasma sheath. This conclusion is based on the calculations by Laframboise and Rubinstein [1976], Betringer and Wa!ker [1965], Miller [1972], and experimental results collected by a pulsed plasma probe flown on a scientific rocket payload (NASA 18.170).…”
mentioning
confidence: 99%